Comparing the Effect of Stabilization Exercises with and without Dry Needling on Pain and Performance of Patients with Chronic Low Back Pain - Mahmood Seify; Amir Letafatkar (Biyumikānīk-i varzishī)
Objective Patients with low back pain have stability defects and trigger points that cause low back pain. The aim of this study was to compare the effect of six-weeks stabilization exercises with and without dry needles on pain and performance in patients with chronic nonspecific low back pain. Methods ISixty-six patients with chronic non-specific low back pain (age 31. 6±2. 3 years, and weight 79. 6±7. 5 kg) were selected and were randomly divided into 2 equal experimental (stabilization exercises with and without dry needles) groups and one control group. At first, patients' pain and function were measured by visual analog scale (VAS) and Qswestry disability questionnaire. Then, the experimental groups underwent an intervention under supervision of the experienced trainer. But the patients in the control group did not exercise and did not receive any interventions. In the posttest stage, pain and performance were evaluated again in the three groups. The SPSS version 20 was used to analyze the data at a significance level of P <0.05. Results IThe results of the study showed a significant improvement in pain and performance of patients in experimental groups following stabilization exercises alone and with dry needling compared to the control group. Conclusion It can be concluded that core stabilization exercises with dry needles have a significant effect on reducing pain in patients with chronic low back pain and also have a significant effect on improving performance. The effect of stabilization exercises with dry needling is superior than stabilization exercises alone; thus, it is recommended that stabilization exercises with dry needling be considered in the treatment plan of patients with chronic low back pain.